2011
DOI: 10.1371/journal.pone.0025812
|View full text |Cite
|
Sign up to set email alerts
|

Shared and Distinct Functions of the Transcription Factors IRF4 and IRF8 in Myeloid Cell Development

Abstract: Interferon regulatory factor (IRF) 8 and IRF4 are structurally-related, hematopoietic cell-specific transcription factors that cooperatively regulate the differentiation of dendritic cells and B cells. Whilst in myeloid cells IRF8 is known to modulate growth and differentiation, the role of IRF4 is poorly understood. In this study, we show that IRF4 has activities similar to IRF8 in regulating myeloid cell development. The ectopic expression of IRF4 in myeloid progenitor cells in vitro inhibits cell growth, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 39 publications
(69 reference statements)
4
67
1
1
Order By: Relevance
“…Nevertheless, IRF8 appears to be involved in tissue-resident Mϕ development as well. The number of bone marrow resident Mϕs in Irf8 −/− mice is significantly lower [28]. Even though Irf8 −/− mice display only a modest decrease in splenic red pulp Mϕs, the loss of both IRF8 and structurally related IRF4 causes a significant decrease in these cells.…”
Section: It Was Initially Thought That Irf8mentioning
confidence: 93%
“…Nevertheless, IRF8 appears to be involved in tissue-resident Mϕ development as well. The number of bone marrow resident Mϕs in Irf8 −/− mice is significantly lower [28]. Even though Irf8 −/− mice display only a modest decrease in splenic red pulp Mϕs, the loss of both IRF8 and structurally related IRF4 causes a significant decrease in these cells.…”
Section: It Was Initially Thought That Irf8mentioning
confidence: 93%
“…However, neutrophilic differentiation is inhibited by the ectopic expression of IRF4 or IRF8, possibly as a result of altered PU.1 expression (Yamamoto et al, 2011;Becker et al, 2012). Presumably because of the lower expression level, IRF4 −/− mice, but not IRF8 −/− mice, exhibit no obvious abnormality in the development of myeloid cells compared with their wild-type controls (Yamamoto et al, 2011). Additionally, IRF8 shows a potent ability to inhibit myeloid cell growth and to promote apoptosis potentially by regulating several key genes, for example Bcl2l1, Nf1 and Bax (Huang et al, 2007;Yang et al, 2011;Scheller et al, 2013).…”
Section: Implication Of Irfs In Immunitymentioning
confidence: 99%
“…Although IRF4 is expressed at a much lower level than IRF8 in granulocyte-macrophage progenitors, both of these IRFs strongly promote the differentiation of CMPs to macrophages. However, neutrophilic differentiation is inhibited by the ectopic expression of IRF4 or IRF8, possibly as a result of altered PU.1 expression (Yamamoto et al, 2011;Becker et al, 2012). Presumably because of the lower expression level, IRF4 −/− mice, but not IRF8 −/− mice, exhibit no obvious abnormality in the development of myeloid cells compared with their wild-type controls (Yamamoto et al, 2011).…”
mentioning
confidence: 99%
“…Indeed, multiple studies have recently demonstrated that deletion of IRF4 in mice leads to the development of B-cell leukemia. [12][13][14][26][27][28][29] …”
Section: Mir-125b Overexpression Induces B-cell Cancer Harboring Irf4mentioning
confidence: 99%